THE PROTOTYPE OF A REBELLIOUS WIDOW IN JAVANESE MYTHOLOGY AS REPRESENTED IN PRAMOEDYA ANANTA TOER'S CALON ARANG: SOCIOLOGICAL PERSPECTIVE - Dharmali, Heidy Sashia (LITERA KULTURA : Journal of Literary and Cultural Studies, 2022)
Abstract: Since a long time ago. The woman who had been left by her husband is always regarded as a bad person, even in reality they are nice. Whether a divorcee or a widow, the depiction from society about them always related to bad things, such as bringing malady to the other married life. In the older days, they always seek as a hideous figures who can harm other people's life. Although she does not want the divorce, sometimes she does not have a choice rather than divorce. This paper is aiming to find shreds of evidence that Calon Arang was not a pure villain, but she was marginalized too by her people. Through the theory of Subaltern, a title about a secluded group of people that was found by Chakravorty Spivak an Indian post-colonist. The result of this research shows that Calon Arang was also a victim of society's stigma about a widow or the divorcee as someone frightening which led her to the rebellion. In the end of the story, her voice was still not sounded and she was defeated yet helped by a man due to society mentality that thought a woman have no voice or right to speak their mind nor fight for herself. Which also represented the other widows or women condition during the era, their voices were shuts and treated as the lower class who is unable to live without the help of a man. Keywords: Stigmatism, Subaltern, Widow Abstrak: Sejak jaman dulu kala. Wanita yang telah ditinggal suaminya selalu dipandang sebagai sosok yang buruk, walau pada kenyataannya mereka tidak. Enthah mereka yang diceraikan hukum atau cerai mati, gambaran masyarakat tentang mereka selalu dihubungkan dengan imaji imaji buruk, seperti membawa petaka bagi pernikahan orang lain. Di masa lampau, mereka dipandang sebagai sosok mengerikan yang bisa membahayakan hidup sesamanya. Padahal dia tidak punya pilihan lain, karena terkadang dia tidak mempunyai pilihan lain selain perceraian. Artikel ini mencoba untuk menemukan bukti bukti terkait jika Calon Arang, bukanlah penjahat yang paling jahat, tapi dia juga terpinggirkan oleh masyarakat di sekitarnya. Melalui teori Subaltern, sebuah julukan untuk orang orang tertindas yang ditemukan Chakravorty Spivak seorang pembuat teori pasca-kolonial. Hasil dari penelitian ini menunjukkan jika Calon Arang juga seorang korban dari stigma masyarakat tentang janda sebagai sosok mengerikan yang nantinya akan menjurus kepada perlawanannya. Di akhir cerita, suaranya tetap tak terdengar dan dia dikalahkan juga ditolong seorang pria. Ini menunjukkan jika wanita maupun janda di masa itu, dibungkam dan diperlakukan sebagai makhluk rendahan yang tak bisa hidup tanpa bantuan dari seorang pria. Kata kunci: Stigmatisme, Subaltern, Janda